Effect of Mind-Body Therapy on Intraocular Pressure in Open-Angel Glaucoma Patients: A Systematic Review - Rondhianto Rondhianto; Siswoyo Siswoyo; Ajeng Dian Sandika (Universitas Aisyah Pringsewu, 2023)
Open-angle glaucoma is one type of glaucoma that can damage the eye's optic nerve, causing blindness. Intraocular Pressure (IOP) is the leading risk factor for open-angle glaucoma. So, controlling IOP is the goal of glaucoma management. One of the complementary therapies that glaucoma patients can choose is a mind-body therapy. The study aims to determine the effectiveness of mind-body therapy on IOP in glaucoma patients. A systematic literature review followed the PRISMA Flowchart guidelines in five databases (PubMed, ProQuest, ScienceDirect, Scopus, and Google Scholar). Inclusion criteria were articles published in the last ten years, English, and experimental studies about mind-body therapy's effect on glaucoma patients' intraocular pressure. The quality of articles was assessed using the JBI appraisal tools and analyzed using Meta-synthesis. We found two types of mind-body interventions that affect IOP: mindfulness meditation and yoga. Twelve articles showed that mind-body intervention had decreased IOP by 2 - 6 mmHg (5.7 - 16%). Only one article showed an increase in IOP (6 mmHg), namely yoga with a head down position (the head position lower than the heart position Mind-body therapy, particularly meditation and yoga, can significantly lower IOP. Special attention in yoga therapy is not to do the head down position because it can increase IOP. Mind-body therapy intervention as a complementary therapy can be applied to glaucoma patients to decrease IOP and prevent blindness. Abstrak: Glaukoma sudut terbuka merupakan salah satu jenis glaukoma yang dapat merusak saraf optik mata sehingga menyebabkan kebutaan. Tekanan intraokular (IOP) adalah faktor risiko utama untuk glaukoma sudut terbuka. Jadi, mengendalikan TIO adalah tujuan dari manajemen glaukoma. Salah satu terapi komplementer yang dapat dipilih oleh pasien glaukoma adalah mind-body therapy. Penelitian ini bertujuan untuk mengetahui efektivitas mind-body therapy terhadap TIO pada pasien glaukoma. Tinjauan literatur sistematis dilakukan mengikuti panduan PRISMA Flowchart di lima database (PubMed, ProQuest, ScienceDirect, Scopus, dan Google Scholar). Kriteria inklusi adalah artikel yang diterbitkan dalam sepuluh tahun terakhir, bahasa Inggris, dan studi eksperimental tentang efek terapi pikiran-tubuh pada tekanan intraokular pasien glaukoma. Kualitas artikel dinilai menggunakan alat penilaian JBI dan dianalisis menggunakan Meta-sintesis. Kami menemukan dua jenis intervensi pikiran-tubuh yang memengaruhi TIO: meditasi mindfulness dan yoga. Dua belas artikel menunjukkan bahwa intervensi pikiran-tubuh telah menurunkan TIO sebesar 2 - 6 mmHg (5,7 - 16%). Hanya satu artikel yang menunjukkan peningkatan TIO (6 mmHg), yaitu yoga dengan posisi head down (posisi kepala lebih rendah dari posisi jantung. Mind-body therapy, khususnya meditasi dan yoga, dapat menurunkan TIO secara signifikan. Perhatian khusus pada yoga Terapi tidak dilakukan dengan posisi kepala menunduk karena dapat meningkatkan TIO. Intervensi mind-body therapy sebagai terapi komplementer dapat diterapkan pada pasien glaukoma untuk menurunkan TIO dan mencegah kebutaan.